Evaluación de dos tratamientos, solución gradiente percoll (45 - 90%) y otra solución con la adición de bicarbonato de sodio en vacas primer parto - Mena Changoluisa, Ángel Gabriel (2014)
The present investigation was carried out in the laboratories of Bossgen of property of the company Produbiogensa and in the “Cortijo de Solanda” Farm, located in the Canton Mejía, County of Pichincha - Ecuador. The main objective of the investigation was to compare the effect of the centrifugación of bovine semen in gradient Percoll and a solution of bicarbonate of sodium, to increase the viability of the sperms X and this way to increase the conception of breedings female in the “Cortijo de Solanda Farm”. To carry out the investigation was used 2 treatments; Treatment 1 (T1) bovine semen centrifuged in gradient Percoll to (90% and 45%), Treatment 2 (T2) bovine semen centrifuged in gradient Percoll to (90% and 45%) with the addition of an uterine laundry using a solution of bicarbonate of sodium with a stocking of 72 hours before the artificial insemination….